Bionic Morse Coding Mimicking Humpback Whale Song for Covert Underwater Communication - Bilal; Liu; Qiao; Wan; Tao (Applied Sciences, 2019)
A novel method of bionic Morse coding mimicking humpback whale vocal is presented for covert underwater acoustic communication. The complex humpback whale song is translated as bionic Morse codes based on information entropy. The communication signal is made akin to the natural singing of male humpback whales. The intruder can detect the signal but will not be able to recognize the communication signal due to unified resemblance with the natural sound. This novel technique gives an excellent low probability of recognition characteristics. A flawless stealthy underwater acoustic communication has been established which has negligible chances of deciphered with high imperceptibility. Standard mimicry Morse codes have been developed for the characters of the English language and compared with Morse coding. Covert information of one character per second can be watermarked with perfect stealth and clandestine communication. This novel concept has been verified at transmission distance of five km and less than 10−3 Bit Error Rate (BER) is achieved at Signal to Noise Ratio (SNR) down to negative seven dB. Zero BER is attained by estimating the channel by a matching pursuit algorithm and equalizing the errors by virtual time reversal mirror technique.